FRUIT RIPENING AND QUALITY OF â€˜KENSINGTON PRIDEâ€™ MANGOES FOLLOWING THE CONTROLLED ATMOSPHERE STORAGE - Sumual, M. F.; Singh, Z.; Singh, S. P.; Tan, S. C. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2017)
Hard mature green â€˜Kensington Prideâ€™ mangoes were stored in normal air (NA) or in controlled atmosphere (CA) chambers with combinations of 3% oxygen (O2) and three concentrations of carbon dioxide (CO2) i.e. CA1: 3%, CA2: 4%, or CA3: 5% at 13â°C for 4 weeks followed by ripening at 21â°C. The effects of CA on fruit quality during ripening were investigated. At fully ripe stage, fruits stored in CA were firmer and greener with concomitant lower reduction of chlorophylls compare to those stored in NA. All CA-stored fuit retained its skin carotenoids during ripening. The reduction of sucrose and glucose concentrations were measured in all CA-stored fruit, and the same condition were also measured for citric acid and succinic acid content during ripening. However, concentration of glucose, citric acid and succinic acid in CA-stored fruit were higher than NA-stored fruit. Pulp carotenoids and ascorbic acid in all CA-stored fruit were higher compare to NA-stored fruit at the ripe stage. The data suggest that CA storage could improve the ripe quality of â€˜Kensington Prideâ€™ mango to some extend.